Identification of Novel and Efficacious Chemical Compounds that Disturb Influenza A Virus Entry in vitro - Khalil, Hany; El Malah, Tamer; El Maksoud, Ahmed I. Abd; El Halfawy, Ibrahim; El Rashedy, Ahmed A.; El Hefnawy, Mahmoud (Frontiers in Cellular and Infection Microbiology, 2017)
Influenza A virus is a negative RNA stranded virus of the family Orthomyxoviridae, and represents a major public health threat, compounding existing disease conditions. Influenza A virus replicates rapidly within its host and the segmented nature of its genome facilitates re-assortment, whereby whole genes are exchanged between influenza virus subtypes during replication. Antiviral medications are important pharmacological tools in influenza virus prophylaxis and therapy. However, the use of currently available antiviral is impeded by sometimes high levels of resistance in circulating virus strains. Here, we identified novel anti-influenza compounds through screening of chemical compounds synthesized de novo on human lung epithelial cells. Computational and experimental screening of extensive and water soluble compounds identified novel influenza virus inhibitors that can reduce influenza virus infection without detectable toxic effects on host cells. Interestingly, the indicated active compounds inhibit viral replication most likely via interaction with cell receptors and disturb influenza virus entry into host cells. Collectively, screening of new synthesis chemical compounds on influenza A virus replication provides a novel and efficacious anti-influenza compounds that can inhibit viral replication via disturbing virus entry and indicates that these compounds are attractive candidates for evaluation as potential anti-influenza drugs.